Le sens accordé à la différenciation pédagogique par des enseignants du secondaire : quels constats pour le projet inclusif ? - Geneviève Bergeron; Gabriel B. Houde; Luc Prud’homme; Virginie Abat-Roy (Éducation et Socialisation)
In Quebec, where the inclusive project is highly associated with the implementation of pedagogical differentiation (PD) in ministerial documents (Ministère de l’Éducation et de l’Enseignement supérieur [MEES], 2017), it is clear that teachers do not feel properly equipped to take action. (Ducharme, 2018). Moreover, it appears that the challenges are compounded in the secondary school system, especially when students with behavioural problems are integrated in the classroom (Bergeron, 2014). This study questions the meaning given to PD by secondary teachers in this specific context. The article presents the results of qualitative research conducted with 12 Quebec teachers. The data collected through a survey and a semi-structured interview show that pedagogical differentiation is based on a reactive and deficit logic of correcting difficulties through individual interventions with students identified as having special needs.